Faktor-Faktor yang Berhubungan dengan Praktik Pemeriksaan Payudara Sendiri (SADARI) pada Siswi Kelas XI MAN I Palembang Tahun 2021 - Windy Yovita Sari; Siti Aisyah; Satra Yunola (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Breast cancer is cancer of the breast tissue. Global Cancer Observatory 2018 data from WHO shows that the most common cancer cases in Indonesia are breast cancer, which is 58,256 (16.7%) of the total 348,809 cancer cases, and in Indonesia it reaches 42.1/100,000 population. The average death rate from this cancer is 17/100,000 of the population. Breast self-examination (BSE) is a form of practice that is influenced by 3 main factors, namely predisposing factors, enabling factors, and reinforcing factors. The purpose of this study was to determine the relationship between knowledge, attitudes and sources of information with BSE practice in MAN 1 class XI Palembang in 2021. Analytical Survey Research with a cross sectional approach. All students of class XI MAN 1 Palembang for the academic year 2021/2022, totaling 168 as the population and 63 samples taken using stratified random sampling technique. The primary data used were analyzed using univariate analysis and bivariate chi square test. The results showed that there was a relationship between knowledge (Pvalue = 0.002), attitude (Pvalue = 0.037) and sources of information (Pvalue = 0.011) with BSE practice at MAN 1 class XI Palembang in 2021. The results of this study are expected to be an illustration to increase information to students about reproductive health such as counseling on BSE practice skills so that students are able to detect abnormalities that occur in the breast as early as possible.